How Does Preoperative Pure Tone Audiometry Relate to the Findings at Surgery to Explain the Hearing Status in Chronic Otitis Media? - Sharafali KADAMBOTT; Prasanta KUMAR GURE; Soumya GHATAK; Mainak DUTTA; Chandan SETH; Saumik DAS; Ramanuj SINHA (Medeniyet Medical Journal)
Objective: Pure tone audiometry (PTA) guides surgical decision-making in chronic otitis media (COM), and PTA values depend upon the type and extent of COM. Methods: Our cross-sectional study included patients with COM with/without cholesteatoma who were scheduled for surgery. Findings on examination of the middle ear under the microscope and at surgery which could explain the hearing loss were corroborated with preoperative PTA through appropriate statistical methods. Results: The study included 114 patients (mean age: 31.07 years; range: 7-57). Following preoperative PTA, 50% of patients had moderate hearing loss and ~73% had air-bone gap (ABG) <35 dB. Conductive hearing loss affected 109 patients (97.61%); five had mixed hearing loss. At surgery, 27 patients (23.68%) had ossicular discontinuity, with the incus being the most affected. Twenty-one patients in this group had ABG ≥35 dB. Perforations involving the anterior and posterior halves of the pars tensa, and subtotal perforations, demonstrated the maximum mean hearing loss [45.39+-8.29 dB HL (p=0.075), 51.08+-12.51 dB HL (p=0.26), respectively]. The mean pure tone average in the intact ossicles group was 43.62+-8.07 dB HL and that in the absent/eroded ossicles group was 58.15+-11.05 dB HL (p<0.0001); the mean ABG was 27.89+-4.77 dB and 38.88+-6.47 dB, respectively (p<0.0001). Conclusions: Hearing loss was significantly associated with the size but not the site of the central perforation. With ossicular discontinuity, hearing loss and ABG deteriorated significantly. The findings re-establish the relationship between preoperative PTA and the middle ear status which should help surgeons plan surgery and counsel patients regarding hearing outcomes.